ANALISIS STRATEGI BERSAING PERUSAHAAN JASA KONSULTASI ENTERPRISE RESOURCES PLANNING (ERP) STUDI PADA PT SOLTIUS INDONESIA - , Setio Candrawati Ningsih, Amin Wibowo, M.B.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research objectives are to define proposed company strategy by doing internal and external analysis with SPACE (Strategic Position and Action Evaluation) Matrix and to define a systematic strategy formulation process which will use to achieve the sustainable competitive advantage. Research was performed at an Enterprise Resources Planning (ERP) consulting firm, which is a member of the biggest information technology group of company in Indonesia. Internal and external analysis were performed by using secondary data, interview and focus group discussion result with the board of directors (president director, sales director and delivery director). The information was analyzed by using SPACE (Strategic Position and Action Evaluation) matrix which defined company strategy and strategy formulation steps according to strategic management theory in order to achive the competitive advantage. The suitable strategic posture is aggressive and the competitive strategy is cost leadership. Currently company is in the growth industry which has high potential, relatively stable environment and financial strength. The company objective is to reduce cost compared to its competitor without sacrificing delivery quality. Strategy definition process is enhanced by adding several steps in strategic management whihc is not implemented yet.